Different Efficacy of Nanoparticle and Conventional ZnO in an Animal Model of Anxiety - Torabi, M.; Kesmati, M.; Harooni, H.E.; Varzi, H.N. (Нейрофизиология, 2013)
As has been shown, trace element supplementation by zinc, e.g., in the form of zinc oxide
(ZnO), can significantly influence the anxiety level. We investigated the effects of ZnO in
the form of nanoparticles (NPs) in comparison with conventional ZnO (cZnO) in an animal
model of anxiety. Adult male Wistar rats were divided into seven groups, control (receiving
0.9% saline) and six groups receiving 5, 10, and 20 mg/kg ZnO NPs and 5, 10, and 20 mg/kg
cZnO. All drugs dispersed in 0.9% saline were injected i.p.; 30 min later, the anxiety level
was estimated according to the results of the elevated plus maze test. ZnO NPs (5 mg/kg)
and cZnO (10 and 20 mg/kg) significantly increased the normalized values of time spent in
open arms (open arm time, OAT, %) in comparison with the control group (P < 0.05). This
is indicative of the anxiolytic effects of these components; in addition, 20 mg/kg ZnO NPs
reduced the intensity of locomotor activity (P < 0.05). The serum zinc concentration was
increased manifold by anxiolytic doses of the components. All doses increased serum pH
to 8.05-8.10 and kept this index constant for 24 h. These results indicate that the anxiolytic
effect of ZnO NPs is much more intense than that of conventional ZnO, but the introduction
of ZnO NP as a new drug for the treatment of anxiety disorders needs further investigations Як було показано, додавання мікроелементу цинку
(наприклад, у формі окису цинку, ZnO) може істотно
впливати на рівень тривожності. Ми досліджували вплив
ZnO у формі наночасток (НЧ) порівняно зі стандартним ZnO
(сZnO) на пов’язану з тривогою поведінку у щурів. Дорослі
щури лінії Вістар були поділені на сім груп – контрольну
групу (тварини отримували фізіологічний розчин) та
шість груп щурів, котрі отримували 5, 10 та 20 мг/кг ZnOНЧ, а також 5, 10 та 20 мг/кг сZnO. Усі дисперговані у
0.9 %-му фізіологічному розчині препарати ін’єкували
внутрішньоочеревинно; через 30 хв після ін’єкції рівень
тривоги оцінювали згідно з результатами тесту піднятого